Development of an LMS-based e-literacy management model for managing the junior high school literacy movement - Oliva Ike Kurniawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research was conducted because the Gerakan Literasi Sekolah (GLS) implementation in junior high schools has not run effectively and efficiently. Although the habit of reading books has been carried out in a scheduled and routine manner, literacy activities have not been managed well, and there are no structured steps. For this reason, the researcher developed an LMS-based E-Literacy management model for managing literacy activities to solve existing problems. This research and development design uses the Borg & Gall model, which is limited to stage 5, namely the main product trial. The research subjects were the principal of a junior high school, teachers or the GLS Team, and students. The resulting product is a Moodle LMS-based E-Literacy management model, model books, and user guides. Research results: 1) The implementation of the Junior High School Literacy Movement was carried out manually. 2) The weaknesses of the Junior High School Literacy Movement management that were carried out included not being managed systematically and not involving technology. 3) The development of the School Literacy Movement management model resulted in a Moodle-based E-Literacy management model with validation results from literacy experts of 87%, ICT experts of 89%, while the average application trial for teachers or literacy teams was 89%, and students were 86%, so based on this, the Moodle-based E-Literacy management model is in the very good category